2020
DOI: 10.3390/fluids5030136
|View full text |Cite
|
Sign up to set email alerts
|

3D Printed Structured Porous Treatments for Flow Control around a Circular Cylinder

Abstract: The use of porous coatings is one of the passive flow control methods used to reduce turbulence, noise and vibrations generated due to fluid flow. Porous coatings for flow stabilization have potential for a light-weight, cost-effective, and customizable solution. The design and performance of a structured porous coating depend on multiple control parameters like lattice size, strut thickness, lattice structure/geometry, etc. This study investigated the suitability of MSLA 3D printers to manufacture porous coat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…The first point of note is the considerable increase in simulation time required, as the time to quasi-steady-state vortex shedding increased by approximately 350% when compared to the smooth case. This is in agreement with both the experimental and numerical literature, all of which found there was a significant delay in shear layer roll up and, thus, vortex shedding [2,[9][10][11][12][13][14][15][16][17][18][19][23][24][25]. Naito et al [14,15] attribute this to the stabilisation of the shear layer as a result of low-energy fluid being injected downstream of the porous layer.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The first point of note is the considerable increase in simulation time required, as the time to quasi-steady-state vortex shedding increased by approximately 350% when compared to the smooth case. This is in agreement with both the experimental and numerical literature, all of which found there was a significant delay in shear layer roll up and, thus, vortex shedding [2,[9][10][11][12][13][14][15][16][17][18][19][23][24][25]. Naito et al [14,15] attribute this to the stabilisation of the shear layer as a result of low-energy fluid being injected downstream of the porous layer.…”
Section: Discussionsupporting
confidence: 87%
“…Bathla and Kennedy [23] investigated the use of 3D-printed porous coatings implemented partially along the span of a cylinder. They concluded that the full porous coatings reduced wake width and turbulence intensity and found that the partial coatings had the potential to provide the same or better turbulence reductions.…”
Section: Introductionmentioning
confidence: 99%
“…This agrees with Sueki et al [29], who showed experimentally that a full porous coating for 4.6 × 10 4 < Re < 8.3 × 10 4 reduces aerodynamic noise and increases the size of the zero velocity region in the cylinder wake, attributing this to the porous coating reducing fluid momentum in the wake and subduing vortex shedding. Bathla and Kennedy [12] showed experimentally that high porosity coatings significantly reduced turbulence in the wake, with a 95% porosity coating offering a 70% reduction in turbulence compared to a smooth cylinder. Hu et al [30] found numerically that partial porous coatings around the separation point can reduce drag by 30% .…”
Section: Porous Coatingsmentioning
confidence: 99%
“…Each has been studied previously in isolation, with numerous studies demonstrating drag reduction using SJAs [4][5][6][7] and porous coatings [8][9][10] when applied to cylinders in crossflow. Porous coatings around cylinders have also been shown to largely suppress oscillating lift forces [11] and reduce noise [12]. Therefore this current study focuses on altering the drag coefficient (C d ) and the root-mean-square (RMS) lift coefficient (C l(rms) ) of a cylinder using these technologies.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike their stochastic counterparts, lattices can be designed with defined dimensions in an ordered arrangement. However, while additively manufactured lattices and periodic structures have been explored in detail for their mechanical and thermal properties, their use in fluid applications remains a high‐potential area 16–22 . Much of the recent investigation into lattices for fluid applications have emerged from studies of open‐cell foams.…”
Section: Introductionmentioning
confidence: 99%